Hizbollah and Today's Battle for Beirut - Harik, Judith Palmer (Tufts Archival Research Center, 2005)
Volume 31, Issue 2. Summer The summer 2006 conflict between Israel and Lebanon revealed the extent that Hizbollah influences domestic and regional politics. As the political standoff continues in Lebanon, Hizbollah retains notable popular support and boasts organizational and military efficacy that have taken the international community by surprise. What implications does Hizbollah's strength have on U.S. foreign policy in the region and where does Lebanon fit in the struggle for Middle East peace?